Impact of Bariatric Surgery on the Quality of Life of Obese Individuals with Chronic Low Back Pain - Gil, Bruno Ziade (2024)
Introduction: Obesity has been increasing at alarming rates in Brazil and worldwide. It is known that bariatric surgery is an effective and safe treatment for severely obese adults with related comorbidities or morbidly obese individuals. Among the various comorbidities, chronic low back pain is one of the major sources of discomfort and reduced quality of life in these patients. Studies that investigate the impact of bariatric surgery on the lives of obese individuals with chronic low back pain are scarce. Methods: We analyzed 38 patients who were obese grade 3 or severely obese grade 2 and suffered from chronic low back pain. These patients underwent bariatric surgery. Eight variables were assessed before the surgery and 6 months post-surgery, comprising 5 quantitative variables and 3 qualitative variables. Results: Paired t-tests were used for the statistical analysis of quantitative variables. The mean values of interleukin-6 before the surgery did not differ statistically from post-operative measurements. However, the values of C-reactive protein, weight, BMI, and Oswestry Disability Index 2.0 were all statistically different post-operatively. As for qualitative variables, the 3 variables analyzed using the Wilcoxon test showed statistically significant differences. Conclusion: Substantial reduction in weight following bariatric surgery may be associated with significant reductions in chronic low back pain in the early post-operative period. This effect could result from an overall improvement in well-being associated with weight loss but may also be associated with a reduction in inflammatory factors, as indicated by the decrease in C-reactive protein, although not confirmed by interleukin-6.